Estimating the welfare costs of very high inflations and hyperinflations - Luca Benati; Juan Pablo Nicolini (University of Bern, Department of Economics, 2024)
We explore the welfare costs of inflation originating from lack of liquidity satiation for Weimar Republic's hyperinflation and three high-inflation countries. Towards the peak of Weimar's hyperinflation the costs are estimated to have been equal to nearly 20 per cent of income. For Israel, Mexico, and Argentina the costs had been materially lower, but still in the range of 3-5 per cent of GDP.
Keywords: 330; Inflation; hyperinflation; social costs; welfare analysis; money demand; estimation; Germany; Mexico; Israel; Argentina; Inflation; Hyperinflation; Soziale Kosten; Wohlfahrtsanalyse; Geldnachfrage; Schätzung; Deutschland; Mexiko; Israel; Argentinien